2001
DOI: 10.1038/sj.bjp.0704290
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cyclooxygenase‐2 protein by lipoteichoic acid from Staphylococcus aureus in human pulmonary epithelial cells: involvement of a nuclear factor‐κB‐dependent pathway

Abstract: 1 This study investigated the role of protein kinase C (PKC) and transcription factor nuclear factor-kB (NF-kB) in cyclooxygenase-2 (COX-2) expression caused by lipoteichoic acid (LTA), a cell wall component of the gram-positive bacterium Staphylococcus aureus, in human pulmonary epithelial cell line (A549). 2 LTA caused dose-and time-dependent increases in COX-2 expression and COX activity, and a dose-dependent increase in PGE 2 release in A549 cells. The LTA-induced increases in COX-2 expression and COX acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 41 publications
3
31
0
Order By: Relevance
“…We also provide data supporting a role for NF-B regulation of COX-2 expression in airway smooth muscle cells that has not been previously reported using this cytokine stimulus. In human lung alveolar epithelial cells and epithelial cell lines, COX-2 expression was found to be mediated by NF-B-dependent signaling pathways (5,18). However, in other studies of airway smooth muscle, lung epithelial cells, and vascular smooth muscle, a role for NF-B in COX-2 expression was not found (6,16,24).…”
Section: Discussionmentioning
confidence: 80%
“…We also provide data supporting a role for NF-B regulation of COX-2 expression in airway smooth muscle cells that has not been previously reported using this cytokine stimulus. In human lung alveolar epithelial cells and epithelial cell lines, COX-2 expression was found to be mediated by NF-B-dependent signaling pathways (5,18). However, in other studies of airway smooth muscle, lung epithelial cells, and vascular smooth muscle, a role for NF-B in COX-2 expression was not found (6,16,24).…”
Section: Discussionmentioning
confidence: 80%
“…Candida albicans was found to upregulate cyclooxygenase (COX)-2 through activation of PKC in epithelial cells [47]. Moreover, pathogen-related expression of COX-2 in Helicobacter pylori-or Staphylococcus aureus-infected epithelial cells was shown to be mediated by PKC activation [48,49]. The current authors recently demonstrated that COX-2 expression and subsequent PGE 2 -synthesis induced by Legionella neumophila infection of the alveolar epithelial cell line A549 was reliant on PKCa and NF-kB activation in lung epithelial cells [28].…”
Section: Pkc Regulates M Catarrhalis-induced Il-8 Release H Slevogtmentioning
confidence: 99%
“…Prostaglandins are synthesized by two isoforms of cyclooxygenases (COX, also named PTGS for "prostaglandinendoperoxide synthases"): COX-1 is a constitutive isoform that maintains cellular homeostasis, whereas COX-2 is an inducible isoform regulated by many proinflammatory stimuli (31). COX-1/2 transform arachidonic acid into prostaglandin H 2 , a precursor of many prostaglandins such as prostaglandin E 2 (PGE 2 ), prostacyclin, and thromboxanes.…”
Section: Ease Analysismentioning
confidence: 99%